From Zaphon to Zion: The Redaction of Psalm 20 - Hogue, Timothy (Journal of Biblical literature, 2025)
Since the discovery of an alternate version of Ps 20 in Papyrus Amherst 63 XII, 11-19, the psalm has been the subject of multiple redaction-critical studies and historical reconstructions. Recent scholarship has used these two texts to reconstruct a northern Israelite hymn underlying them both. In this article, I use methods derived from inner-biblical discourse and ideological redaction criticism to shift focus from what was original to the poem to what was changed and why. Instead of further reconstructing the Israelite context for the original poem's composition, I aim to reconstruct the Judahite context for its redaction. Editorial work on the poem was carefully marked using known scribal techniques. Replacements and insertions in the poem were carried out strategically to introduce Judahite ideological fixtures while simultaneously preserving the structure of the original Israelite poem and some of the north's traditions. The result was a pan-Israelite text imagining the integration of the two communities in Judah. I argue that the most likely context for such a redactional enterprise was among the mixed scribal community that emerged in Judah after the fall of the Northern Kingdom.